2022
DOI: 10.3390/jof8101093
|View full text |Cite
|
Sign up to set email alerts
|

Oral Chronic Hyperplastic Candidiasis and Its Potential Risk of Malignant Transformation: A Systematic Review and Prevalence Meta-Analysis

Abstract: Chronic hyperplastic candidiasis (CHC) is a prototypical oral lesion caused by chronic Candida infection. A major controversy surrounding CHC is whether this oral lesion owns malignant transformation (MT) potential. The aim of the present study was to evaluate current evidence on the MT of CHC and to determine the variables which have the greatest influence on cancer development. Bibliographical searches included PubMed, Embase, Web of Science, Scopus and LILACS. The cohort studies and case series used to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…The chosen strains encompass those commonly associated with saprophytic growth and/or those implicated in oral candidiasis. To address this, we included two distinct strains of C. albicans and three strains of non- albicans Candida which are frequently encountered in patients with intact immune systems alongside cancer [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The chosen strains encompass those commonly associated with saprophytic growth and/or those implicated in oral candidiasis. To address this, we included two distinct strains of C. albicans and three strains of non- albicans Candida which are frequently encountered in patients with intact immune systems alongside cancer [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional differential diagnoses that may exhibit similarities and clinical resemblance in presentation such as chronic hyperplastic candidiasis, which is a prototypical oral lesion resulting from chronic Candida infection. characterized by its typical presentation in the anterior buccal mucosa bilaterally with diffuse margins [ 24 , 25 ]. There may also be frictional keratosis induced by mechanical irritation.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperplastic candidiasis may be associated with epithelial dysplasia. A recent systematic review and meta-analysis of 9 observational studies (274 patients) reported a malignant transformation rate of 12.1% (95% CI, 4.1% to 19.8%) . However, the current evidence is insufficient to consider hyperplastic candidiasis as an oral potentially malignant disorder, and a proper diagnostic criterion for hyperplastic candidiasis must be developed.…”
Section: Methodsmentioning
confidence: 99%